Dye-sensitized solar cell: Effect of light on N3 dye/BMII electrolyte based architecture - Okutan, Mustafa; Yakuphanoğlu, Fahrettin; Okutan, Mücteba Ibrahim; Bablich, Andreas; Haring Bolívar, Peter (Elsevier B.V., 2024)
This study evaluates the photovoltaic performance of Dye-Sensitized Solar Cells (DSSCs) for various light conditions. This work focuses on exploring the experimental characteristics of a thin-film solar cell composed of an ITO/TiO2/N3-Dye and BMII electrolyte molecules/Pt/ITO. A meticulous investigation is conducted to understand the impact of different illumination intensities on the efficiency of these solar cells. In the experiments, the power conversion efficiencies (PCE) of the device reached 7.61 % with a maximum open-circuit voltage (Voc) of 0.67 V under 100 mW/cm2 AM 1.5 solar irradiance. The morphology of the TiO2 nanoparticles that have been synthesized for the DSSC were analyzed by Ultraviolet–Visible Spectrometry, X-Ray Diffractometry, as well as Scanning Electron Microscopy and Atomic Force Microscopy. Electrochemical impedance spectroscopy (EIS) parameters and Nyquist plot results showed that a systematic understanding of charge transfer within the DSSC is essential to extract an equivalent circuit model. The results of this study allow optimizing the performance of future DSSCs for sustainable energy systems. © 2024 The Authors
Keywords: BMII electrolyte; DSSC; N3 dye; Photovoltaic cell efficiency; Solar simulator; TiO2 nanoparticles